Pain and the unstable knee - Arner, Justin W.; Jiang, Kevin N.; Musahl, Volker; Fu, Freddie H. (Annals of Joint; Vol 2 (December 2017): Annals of Joint, 2017)
Causes of knee pain in the unstable knee can be multifactorial and complex and often misdiagnosed. Commonly ligamentous injury, such as anterior cruciate ligament (ACL) tears can lead to knee pain that can be secondary to hemarthrosis, articular injuries, meniscal pathology and/or patellofemoral pain. Controversy exits regarding the role bone bruising plays in ACL injured and knee instability patients. Patient factors such as sex, age, BMI, and type of sport play a role as well. When ligamentous reconstruction is chosen, prehabilitation is essential to decrease the risk of arthrofibrosis which is a common cause of post-operative knee pain. Autograft donor site pain, as well as painful hardware, also is relevant. Post-operative therapies are critical as well. Posterior cruciate ligament (PCL) injury can lead to asymptomatic instability which also can be a cause of pain. As with the ACL, this instability can lead to further cartilage damage and osteoarthritis and subsequently to knee pain. Further, multi-ligamentous knee injuries are complex and causes of knee pain are even more numerous. Special attention must be paid to the vascular and neurologic status of the patient as conditions such as complex regional pain syndrome can be devastating. Commonly, injury and surgical complications, and arthrofibrosis can cause acute and chronic pain and no superior treatment scheme has been well established. The authors recommend an individualized approach with a thorough exam, appropriately indicated treatments, and post-operative care to prevent further injury and debilitating pain to allow the best outcomes.